Sustainability of global fashion brands and attitudes of consumers from different generations in the Czech Republic - Servusová, Štěpánka (2025)
This thesis is focused on the sustainability of global fashion brands with the aim to evaluate the attitudes of consumers across different generations on the Czech market towards the sustainability of global fashion brands. The theoretical part of the thesis provides the reader with an overview of the fashion industry, the ethical and environmental challenges it faces, and it also addresses how fashion brands react to these issues. It takes a closer look at the Czech fashion market and subsequently mentions the consumer behavior and attitudes towards sustainability of selected generations. The practical part of the thesis is based on a survey, and it evaluates and compares the attitudes of consumers on the Czech market from different generations: Baby boomers, Generation X, Generation Y and Generation Z. It evaluates consumer attitudes toward fashion and subsequently also sustainable fashion as it explores the influence of various factors on their behavior. Finally, recommendations for global fashion brands are offered to increase awareness of their sustainability initiatives and to reach a broader range of consumers.